The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1161/01.cir.0000055189.18831.b1
|View full text |Cite
|
Sign up to set email alerts
|

Marburg I Polymorphism of Factor VII–Activating Protease

Abstract: Background-Atherothrombosis is a main pathomechanism in the evolution of vessel stenosis and is counteracted by endogenous fibrinolysis. Recently, the plasmatic serine protease "factor seven-activating protease" (FSAP) was recognized as a potent activator of prourokinase in vitro. The Marburg I polymorphism of FSAP impairs this potential and may thus facilitate arterial thrombosis. Methods and Results-This analysis of the Bruneck Study involved 810 men and women aged 40 to 79 years. The ultrasound-based athero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…It was recently shown that FSAP reduces cell proliferation of human umbilical vein endothelial cells (52) as well as VSMC (26). Together with the observed presence of FSAP in atherosclerotic lesions and the identification of a single nucleotide polymorphism (Marburg I) as a risk predictor of carotid stenosis (53), FSAP was suggested to be an important inhibitor of the proatherogenic phenotype of VSMC (26). In the present study, we demonstrated that PAI-1 can antagonize the FSAP-mediated inhibition of VSMC proliferation, underscoring the functional relevance of FSAP inhibition by PAI-1 and its possible involvement in cellular activities associated with cell proliferation.…”
mentioning
confidence: 77%
“…It was recently shown that FSAP reduces cell proliferation of human umbilical vein endothelial cells (52) as well as VSMC (26). Together with the observed presence of FSAP in atherosclerotic lesions and the identification of a single nucleotide polymorphism (Marburg I) as a risk predictor of carotid stenosis (53), FSAP was suggested to be an important inhibitor of the proatherogenic phenotype of VSMC (26). In the present study, we demonstrated that PAI-1 can antagonize the FSAP-mediated inhibition of VSMC proliferation, underscoring the functional relevance of FSAP inhibition by PAI-1 and its possible involvement in cellular activities associated with cell proliferation.…”
mentioning
confidence: 77%
“…9 Rare genetic variants (e.g. the Marburg I polymorphism) in HABP2 have also been associated with increased risk of deep venous thrombosis, 24 carotid stenosis, 25 and stroke. 26 Recent animal studies have also suggested that FSAP activity may modulate stroke-associated brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…HABP2 is believed to affect vascular smooth muscle cell proliferation and atherosclerotic plaque instability (27). A HABP2 polymorphism has been associated with inhibited activation of prourokinase and progression of carotid stenosis (28), and HABP2 variants have been associated with venous thromboembolic disease (29). …”
Section: Discussionmentioning
confidence: 99%